Causal relationship between PCSK9 inhibitor and primary glomerular disease: a drug target Mendelian randomization study - Duan, Hangyu; Shi, Yue; Zhang, Qi; Shi, Xiujie; Zhang, Yifan; Liu, Jing; Zhang, Yu (Frontiers in Endocrinology, 2024)
Background: Successive observational studies have identified low-density lipoprotein cholesterol (LDL-C) as an independent risk factor for the progression of CKD to End-Stage Renal Disease (ESRD). Lowering LDL-C levels significantly reduces the incidence of atherosclerotic events in patients with progressive CKD. Recent research indicates that PCSK9 inhibitors not only effectively lower LDL-C levels in CKD patients but also exhibit therapeutic potential for autoimmune diseases like systemic lupus erythematosus, rheumatoid arthritis, and ulcerative colitis. However, the role of PCSK9 inhibitors (PCSK9i) in treating CKD beyond lowering LDL-C levels remains uncertain. Therefore, this study employs drug-targeted Mendelian Randomization (MR) to investigate the causal impact of PCSK9i on primary glomerular diseases such as IgAN, MN, and NS. Methods: Single nucleotide polymorphisms (SNPs) associated with LDL-C were sourced from the Global Lipids Genetics Consortium genome-wide association study (GWAS). Genes situated in proximity to HMGCR and PCSK9 served as proxies for the therapeutic inhibition of these targets. Drug-target MR analyses were performed to determine the causal relationship between PCSK9i and the risk of primary glomerular diseases. HMGCR inhibitor, a drug target of statins, was utilized for comparative analysis with PCSK9i. Primary outcomes included the risk assessment for IgAN, MN, and NS, using the risk of Coronary Heart Disease (CHD) as a positive control. Results: The inhibition of PCSK9, as proxied genetically, was found to significantly reduce the risk of IgAN (OR [95%CI] = 0.05 [-1.82 to 1.93], p = 2.10×10 -3 ). Conversely, this inhibition was associated with an increased risk of NS (OR [95%CI] = 1.78 [1.34 to 2.22], p=0.01). Similarly, HMGCR inhibitors (HMGCRi) demonstrated a potential reduction in the risk of IgAN (OR [95%CI] = 0.0032 [-3.58 to 3.59], p = 1.60×10 -3). Conclusions: PCSK9i markedly decreased the risk of IgAN, suggesting a potential mechanism beyond their primary effect on LDL-C. However, these inhibitors were also associated with an increased risk of NS. On the other hand, HMGCRi appears to serve as a protective factor against IgAN.Conversely, PCSK9i may pose a risk factor for NS, indicating a need for cautious application and further investigation into their effects on different glomerular diseases.